Kerugian Keuangan Negara Dalam Pengadaan Alat Kesehatan Di Indonesia - Ahmad Feri Tanjung; Rizkan Zulyadi; Ronald Hasudungan Sianturi (Jurnal Hukum IUS QUIA IUSTUM, 2019)
he financial loss of the state is determined by many factors leading the method of calculating the state financial loss  to  be  unstandard  and  then  causing  uncertainty in  calculation  of  the  state  financial  loss,  including  in  the procurement of medical devices. This study aims to (a) analyze the factors determining the financial loss of state in the procurement of medical devices and (b) to analyze the method used to calculate the financial loss of the state in the procurement of medical devices. This is a normative juridical research using a conceptual approach and a regulatory approach. The data used were secondary data collected through literature. From the research results, first, it can be concluded that the factors determining the fiancial loss of state in the procurement of medical devices were the factors of goods effectiveness as needed. The procurement of medical devices that has the nature of the goods is a unit to be  utilized as needed, and then the method of calculating the financial loss of state used is the method of calculating the total loss, but if the medical devices that have properties can be utilized separately,  the  calculation  of  financial  losses  used  is  net  loss.  Another  factor  affecting  was  the  price reasonableness if the procurement of medical devices can be utilized as needed but the price of medical devices exceeds the reasonableness. Second, the method of calculating financial loss of stated used due to the price reasonableness was the price reasonableness method.